2019
DOI: 10.1111/plb.13021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead on the physiological, biochemical and ultrastructural properties of Leucaena leucocephala

Abstract: Heavy metals are characterised by a relatively high density and cause genotoxic, cytotoxic and mutagenic effects on plants, animals and humans. Lead (Pb) is one of the heavy metals that causes toxicity to plants and animals.• This experiment was conducted using a hydroponic technique to study the effects of Pb(NO 3 ) 2 on physiological, biochemical and ultrastructural characteristics in Leucaena leucocephala seedlings. Plants were grown in a growth chamber for 21 days in Hoagland's solution supplemented with 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Given their direct contact with the external environment, stomata are considered to be an important apparatus for plants to adapt to environmental stress [6][7][8][9]. An increasing number of studies have shown that heavy metal exposure can cause damages in the structure and function of plant stomata, and ultimately lead to changes in plant physiology and ecology [4,[10][11][12]. Our analysis revealed an increasing interest in the study of stomata under heavy metal stress (Figure 1); the systematic understanding of the effects of heavy metals on plant stomata is still limited because research on the interactions between heavy metals and stomata is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Given their direct contact with the external environment, stomata are considered to be an important apparatus for plants to adapt to environmental stress [6][7][8][9]. An increasing number of studies have shown that heavy metal exposure can cause damages in the structure and function of plant stomata, and ultimately lead to changes in plant physiology and ecology [4,[10][11][12]. Our analysis revealed an increasing interest in the study of stomata under heavy metal stress (Figure 1); the systematic understanding of the effects of heavy metals on plant stomata is still limited because research on the interactions between heavy metals and stomata is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, cadmium promoted a significant reduction in biomass production, height, root parameters, and inhibited the production and expansion of leaves in potato ( solanum tuberosum ) plants at 50 µM 11 , and inhibited growth of wheat plants by accumulation of Cd in plant tissue 36 . Pb significantly reduced shoot height, root length, and dry mass in Leucaena leucocephala seedlings at 300–700 µM Pb (NO 3 ) 2 37 . Intuitively, application of S. platensis under heavy metals stress revealed a much greater ability to promote the growth of rosemary plants compared with untreated plants.…”
Section: Discussionmentioning
confidence: 94%
“…In this connection, Cd-negatively affected plant photosynthetic enzyme activity, pigment content, leaf stomatal conductance, induced chlorophyll degradation, and disorder in grana and thylakoids arrangements, resulting in decreased photosynthesis rate, and chlorophyll content in potato plants 11 . According to 37 chlorophyll decreases in Leucaena leucocephala seedlings have been attributed to Pb (NO 3 ) 2 at 300–700 µM induced chlorophyll synthesis inhibition. In another research, stress of cadmium (10 and 40 mg kg −1 ) and lead (60 and 180 mg kg −1 ) significantly decreased chl a, chl b, chl a + b and carotenoid in Matricaria chamomilla 46 .…”
Section: Discussionmentioning
confidence: 99%
“…And possibly a decrease in photosynthetic pigments as a result of the negative effects of heavy elements in the plant (AL-Rashedy, 2020). And Plants treated with heavy metals had a decrease in the rate of photosynthesis, stomata conduction and transpiration rate (Alkhatib et al, 2019) This is one of the reasons that reduce the process of carbohydrate formation. This is similar to what was found (Selvaraj, 2018) in that the exposure of black gram plants to toxic concentrations of nickel led to a decrease in the concentration of photosynthetic pigments such as chlorophyll and carotenoids due to an imbalance in cellular systems, and this negatively affects the concentration of carbohydrates, which is the main product of the photosynthesis optical.…”
Section: Carbohydrate Concentrationmentioning
confidence: 99%